Angelman Syndrome. Part 3 (Differential Diagnosis and Treatment) - O.Ye. Abaturov; L.L. Petrenko; O.L. Kryvusha (Zaslavsky O.Yu., 2015)
The article discusses the problem of differential diagnosis and treatment of patients with Angelman syndrome (AS). It provides the most common syndromes with similar to AS phenotypes, the main differences between AS-like syndromes, indicating the causative gene. Much attention is given to the basic directions of treating patients with Angelman syndrome: organization of regime, syndromic treatment, providing psychological, speech therapy, orthopedic services, occupational therapy, activities aimed at social adaptation. This article contains the latest information about modern progressive directions of AS medical management. To optimize the diagnostic and therapeutic process, data about international Angelman syndrome foundations are shown.